The States of Uncertainty and Confidence of Asian Immigrants during Their Settlement in South Australia. Issue 2 (2nd April 2020) - Khoir, Safirotu; Du, Jia Tina
ABSTRACT: Migrating to a new land is not always easy and smooth although preparations have been made to tackle challenges ahead. This paper discusses the instances of uncertainty and confidence faced by Asians and associated life experiences as they migrated to Australia, acknowledging the important roles of public libraries. The study collected 197 survey questionnaires, 258 photos, and 35 post-photo interviews. The data were analysed by using descriptive analysis, participatory analysis, and open coding. A process model was developed to illustrate the connections between uncertainty and confidence experienced by Asian immigrants and the generation of social capital, and social inclusion in their migration journey.